The Ethical Dimension of Land as Mother in the Perspective of Yawa Unat Indigenous Communtiy - Limbu, Anggun; Nenohai, Jear (Satya Widya: Jurnal Studi Agama, 2023)
Since ancient times, Yawa Unat have indigenous community revered the land as Mother. The land is a precious and vital resource for indigenous peoples. Nevertheless, the area considered sacred has a very significant economic worth for survival. Realizing that they had lost their land rights and their relationship with the land during the preceding decade, the Yawa Unat sold the land. The land is not simply a mother whose womb gives birth to and enriches the lives of the Yawa Unat Tribe's people. So far, study on Yawa Unat has focused mostly on the economic and religious significance of land as mom. Consequently, the struggle of the Yawa Unat tribe to defend their land is viewed as concentrated solely on their own interests. Furthermore, in this research, utilizing Carolyn Merhant's feminist approach, we suggest that land as a mother has a significant value for the balance of the ecosystem of life for both Yawa Unat and the people of Papua and the natural world of Papua holistically. Therefore, the ethical aspect of Yawa Unat's battle has a significant global impact on the human-nature interaction in Papua. Lastly, this research is limited to ethical considerations and does not yet address features of local religious politics and religious liberty that are crucial to this topic.